Dual Transcriptome Analysis Reveals the Changes in Gene Expression in Both Cotton and Verticillium dahliae During the Infection Process - Yongtai Li; Yuanjing Li; Qingwen Yang; Shenglong Song; Yong Zhang; Xinyu Zhang; Jie Sun; Feng Liu; Yanjun Li (Journal of Fungi, 2024)
Cotton is often threatened by Verticillium wilt caused by V. dahliae. Understanding the molecular mechanism of V. dahlia–cotton interaction is important for the prevention of this disease. To analyze the transcriptome profiles in V. dahliae and cotton simultaneously, the strongly pathogenic strain Vd592 was inoculated into cotton, and the infected cotton roots at 36 h and 3 d post infection were subjected to dual RNA-seq analysis. For the V. dahliae, transcriptomic analysis identified 317 differentially expressed genes (DEGs) encoding classical secreted proteins, which were up-regulated at least at one time point during infection. The 317 DEGs included 126 carbohydrate-active enzyme (CAZyme) and 108 small cysteine-rich protein genes. A pectinesterase gene (VDAG_01782) belonging to CAZyme, designated as VdPE1, was selected for functional validation. VdPE1 silencing by HIGS (host-induced gene silencing) resulted in reduced disease symptoms and the increased resistance of cotton to V. dahliae. For the cotton, transcriptomic analysis found that many DEGs involved in well-known disease resistance pathways (flavonoid biosynthesis, plant hormone signaling, and plant–pathogen interaction) as well as PTI (pattern-triggered immunity) and ETI (effector-triggered immunity) processes were significantly down-regulated in infected cotton roots. The dual RNA-seq data thus potentially connected the genes encoding secreted proteins to the pathogenicity of V. dahliae, and the genes were involved in some disease resistance pathways and PTI and ETI processes for the susceptibility of cotton to V. dahliae. These findings are helpful in the further characterization of candidate genes and breeding resistant cotton varieties via genetic engineering.